AIDS presenting as focal segmental membranous glomerulopathy. Issue 2 (February 1994) - Bass, P S; Garrett, P J; Ellison, D W; Terry, P; O'Connell, S; Theaker, J M; Dathan, J R; Fine, D
Abstract : The case of a young, heterosexual man who was investigated for proteinuria is reported. A renal biopsy specimen showed a focal and segmental membranous glomerulopathy. He was later found to be HIV positive and died from cerebral infarction associated with HIV vasculitis 16 months after his initial presentation. Unusual forms of immune complex mediated glomerulopathies should alert the pathologist to the possibility of HIV associated disease.